Transformation of raw feather waste into digestible peptides and amino acids. Issue 6 (4th March 2016) - Stiborova, Hana; Branska, Barbora; Vesela, Tereza; Lovecka, Petra; Stranska, Milena; Hajslova, Jana; Jiru, Monika; Patakova, Petra; Demnerova, Katerina
ABSTRACT: BACKGROUND: Millions of tons of feather waste from the poultry industry are disposed of annually despite containing a high level of keratin. The aim of this study was to compare the hydrolysis of non‐treated feather waste using three different approaches (whole cell microbial digestion, enzymatic and chemical cleavage) and to test the use of hydrolysates as peptone substitutes in a culture medium. RESULTS: Among bacterial isolates, Pseudomonas sp. P5 exhibited the highest keratinolytic activity and efficiency to hydrolyse raw feather material. The hydrolysates contained up to 301 mg L −1 of free amino acids and 6.2 g L −1 of peptides. Hydrolysates obtained by digestion using semi‐purified keratinase from Pseudomonas sp. P5 were richer in amino acids (1191 mg L −1, 56% essential ones) but peptides were present in lower amounts (up to 3.3 g L −1 ). The third approach was feather treatment under mild alkaline conditions. This provided the highest amount of peptides (17.2 g L −1 ) but a significantly lower level of amino acids, especially the essential ones. CONCLUSIONS: All approaches tested could convert raw feather waste into products of commercial value with proven use in a cultivation medium. The level of peptides, their molecular size and amino acid composition was dependent on the method used. © 2016 Society of Chemical Industry